2020
DOI: 10.1016/j.heliyon.2020.e05652
|View full text |Cite
|
Sign up to set email alerts
|

Improving Alzheimer's stage categorization with Convolutional Neural Network using transfer learning and different magnetic resonance imaging modalities

Abstract: Background Alzheimer's Disease (AD) is a neurodegenerative disease characterized by progressive loss of memory and general decline in cognitive functions. Multi-modal imaging such as structural MRI and DTI provide useful information for the classification of patients on the basis of brain biomarkers. Recently, CNN methods have emerged as powerful tools to improve classification using images. New Method In this paper, we propose a transfer learning scheme using Convoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…They proposed different combination techniques to ensure the best classification. Aderghal et al (29) suggested the transfer learning technique to perform the fusion process and Marzban et al (30)adopted a cascaded CNN. However, they achieved lower accuracy than what we got which is over 97%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They proposed different combination techniques to ensure the best classification. Aderghal et al (29) suggested the transfer learning technique to perform the fusion process and Marzban et al (30)adopted a cascaded CNN. However, they achieved lower accuracy than what we got which is over 97%.…”
Section: Discussionmentioning
confidence: 99%
“…After that, the pre-trained VGG16 network is used to extract the features and SVM classifier to discriminate MCI patients, from CN using the ADNI dataset. Aderghal et al (29) proposed LeNet-like CNN based on sMRI and DTI-MD images. They selected the median slice Hippocampal and its two neighbors in each projection (axial, sagittal, and coronal).…”
Section: Introductionmentioning
confidence: 99%
“…They can produce promising results that outperform human capabilities in various decision tasks relating to visual content classification and understanding such as face detection, 1 object detection and segmentation, 2 image denoising, 3 video-based tasks such as sports action recognition 4 and saliency detection, 5 and among others. The success of deep learning-based systems in these tasks have also paved the way for their applications to be developed for a variety of medical diagnosis tasks such as cancer detection 6 and Alzhiemer's disease detection 7 on different imaging modalities just to name a few. Along with the usefulness of these tools, the trustfulness and reliability of such systems are also being questioned.…”
Section: Introductionmentioning
confidence: 99%
“…They can produce promising results that outperform human capabilities in various decision tasks relating to visual content classification and understanding such as face detection, 1 object detection and segmentation, 2 image denoising, 3 video-based tasks like sports action recognition 4 and saliency detection 5 amongst others. The success of deep learning-based systems in these tasks have also paved the way for their applications to be developed for a variety of medical diagnosis tasks like cancer detection, 6 and Alzhiemer's disease detection 7 on different imaging modalities just to name a few. Along with the usefulness of these tools, the trustfulness and reliability of such systems is also being questioned.…”
Section: Introductionmentioning
confidence: 99%